Pengaruh Tata Kelola Perusahaan, Modal Intelektual dan Pengungkapan Laporan Keberlanjutan terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi (Studi pada Perusahaan yang Terdaftar di LQ 45 Periode 2014-2017) - Dewi, Nurrahma; Kamaliah, Kamaliah; Silfi, Alfiati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This purpose of this research is to test the influence of corporate governance which proxied by institutional ownership, audit commitee and independent commissioner board, intellectual capital and sustainability report disclosure on firm value with financial performance as mediating variable. The population are 45 companies listed on LQ 45 index during 2014-2017. The sampling method is purposive samping, so that obtained about 18 companies a sample. This research uses secondary data obtained in the form of annual reports and sustainability reports. Data analysis technique in this research uses path analysis with SPSS IBM 25.The result of hypothesis testing found that institutional ownership and sustainability report have an effect on firm value, while audit commitee, independent commissioner and intellectual capital have no effect on firm value. Financial performance ia able to mediate audit commitee, independent commissioner, intellectual capital and sustainability report on firm value. Meanwhile, financial performance is unable to mediate institutional ownership and firm value. The results of this research found that corporate governance which proxied by institutional ownership, audit commitee and independent commissioner board, intellectual capital and sustainability report disclosure effect on firm value about 54,5%. While the remaining are influenced by other variables.